(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Non-performing Asset is a crucial factor in the examination of financial performance of a bank. Non-Performing Asset is the key term for the banking corporations. Non-Performing Assets demonstrate the capability of the execution of the banks. Non-performing Assets implies which sum isn’t gotten by the bank consequently of loans dispensed. Non-performing Assets influence the finance establishment as well as the aggregate financial system. Along these lines a particular report has been done on public sector banks in India to assess the impact of Non-performing Assets on the gainfulness of banks. Banks today are not judged just based on number of branches and volume of stores yet additionally based on standard of benefits. NPAs contrarily impact on the gainfulness, liquidity and dissolvability of the banks. This paper analyses the conditions of NPAs in selected banks to be specific State Bank of India (SBI), Bank of India, and United Bank of India, Bank of Baroda, Indian Overseas Bank, Punjab National Bank and Central Bank India. It additionally a feature the approaches took after by the banks to handle the NPAs and recommends a multi-pronged methodology for rapid recuperation of NPAs in banking sector. Seven Public-sector Banks has been chosen for the examination the connection between Gross NPA and Net Profit of seven banks. In this paper is applying the board relapse. The result shows that aside from SBI and PNB all the other banks display a negative relationship between’s their gross Nonperforming Assets and net profits. Be that as it may, SBI and PNB is expanded the net profit consistently not influenced by Gross Non-performing Assets. Both banks are focusing towards their NPA to recuperate their pending loans. The investigation depends on secondary data recouped from Report of Progress of banking in India, Websites, Journals and Articles. The scope of the study is restricted to investigation of nonperforming assets of public sector banks covering the time of 2007-2016.